An Analysis Of Urban Expansion In And Around The Imphal City, Manipur (Journal of Namibian Studies : History Politics Culture, 2023)
Understanding of urban sprawl analysis at the regional scale is of utmost importance in a wide range of application such as land-use  planning and land management. Thus, in this study different prospects of time in a decadal manner  such  as 1988, 1998, 2008 and 2018 along with  Landsat 5 and 8 images have been used. Prior to use, image enhancement procedures, for example, histogram equalisation, radiometric correction are done  keeping in mind the end goal to enhance the perceivability and interpretability of the images. Thus, the images are being  put  as subset and classified into 5 land-use and land cover classes. Furthermore, Shannon Heterogeneity Diversity Indices (SHDI) and Landscape Shape Indices (LSI) in like manner helps in understanding the example and checke the arranged and impromptu nature of the examination region. Thus, the study area is been characterised by a large  increase in the built-up land on the southern side as compared to the remaining sides.